The Future of Performance Reviews: Embracing Continuous Feedback Systems - Tanjung, Febrina Soraya; Karlinda, Ai Elis; Sari, Desi Permata (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study investigates the influence of continuous feedback systems on employee engagement and performance within PT. HM Sampoerna Tbk, a leading tobacco company in Indonesia. Using a quantitative research design, data were collected from a sample of 70 employees through surveys. The analysis employed Structural Equation Modeling (SEM) with SmartPLS software to examine the direct and indirect effects of continuous feedback systems and employee job satisfaction on employee engagement and performance. The results indicate significant direct effects of continuous feedback systems on both employee engagement and performance. Moreover, employee engagement was found to mediate the relationship between continuous feedback systems and performance. However, the indirect effect of employee job satisfaction on performance through engagement was nonsignificant. These findings highlight the importance of continuous feedback systems in fostering employee engagement and performance within the organization, suggesting the need for organizations to prioritize the implementation of effective feedback mechanisms to enhance workforce effectiveness and organizational success.